Fuel Injection - Siano, Daniela (IntechOpen, 2010)
Fuel Injection is a key process characterizing the combustion development within Internal Combustion Engines (ICEs) and in many other industrial applications. State of the art in the research and development of modern fuel injection systems are presented in this book. It consists of 12 chapters focused on both numerical and experimental techniques, allowing its proper design and optimization.